2008
DOI: 10.3174/ajnr.a1015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carotid Atherosclerosis and Detection of Soft Plaque with Use of Black-Blood MR Imaging

Abstract: BACKGROUND AND PURPOSE:In the treatment of carotid atherosclerosis, the rate of stenosis and characteristics of plaque should be assessed to diagnose vulnerable plaques that increase the risk for cerebral infarction. We performed carotid black-blood (BB) MR imaging to diagnose plaque components and assess plaque hardness based on MR signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 41 publications
(49 reference statements)
1
83
0
1
Order By: Relevance
“…[9][10][11] Several imaging modalities have been used to detect unstable plaques by characterizing intraplaque features. Unstable plaques are characterized by mobility and/or low echogenicity on ultrasonography, low attenuation on CT, and hyperintensity on MR imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] Several imaging modalities have been used to detect unstable plaques by characterizing intraplaque features. Unstable plaques are characterized by mobility and/or low echogenicity on ultrasonography, low attenuation on CT, and hyperintensity on MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Various imaging protocols and techniques have been applied in MR plaque imaging, and the results in previous reports have varied. 5,7,[10][11][12][13]16,17 Of these protocols, an electrocardiographgated 2D fast SE technique with a black-blood method is commonly applied. 10,16 However, this method is generally complicated and time-consuming and can obtain only a few sections of imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10) In this study, the patients were divided into two groups: a group with an SIR of ≥1.5, at which plaque fragility may increase, and a group with an SIR of <1.5. 10,11) Furthermore, some studies reported that plaques detected as a high signal intensity on time of flight (TOF) images were fragile 12,13) and we also confirmed findings on TOF images, and retrospectively examined the presence or absence of a high signal intensity in the plaque area in previous patients. Furthermore, it was indicated that plaques in patients with symptomatic lesions were more fragile than in those with asymptomatic lesions; therefore, the results were examined with respect to the presence or absence of symptoms.…”
Section: Plaque Assessmentmentioning
confidence: 99%
“…[2][3][4] Fibrous cap, lipid-rich necrotic core, and intraplaque hemorrhage can be distinguished by studying the signal pattern of plaque on images acquired by T 1 -(T 1 W) and T 2 -weighted (T 2 W) imaging.…”
Section: Introductionmentioning
confidence: 99%